Comparison of Covalent and Noncovalent Immobilization of Malatya Apricot Pectinesterase (Prunus armeniaca L.) - Karakus, Emine; Pekyardimci, Sule (INFORMA HEALTHCARE, 2012)
Pectinesterase isolated from Malatya apricot pulp was noncovalently and covalently immobilized onto bentonite and glutaraldehyde-containing amino group functionalized porous glass beads surface at pH 8.0 and pH 9.0, respectively. The effect of various parameters such as pH, temperature, activation energy, heat and storage stability on immobilized enzyme were investigated. The optimum temperature of covalently and noncovalently immobilized PE was 50 degrees C. This value was 60 degrees C for free PE. Although optimum pH of covalently-immobilized PE was 8.0, this parameter was 9.0 for free and covalently-immobilized PE. The noncovalently immobilized enzyme exhibited better thermostability than the free and covalently immobilized PE.
Keywords: Pectinesterase; Purification; Bentonite; Adsorption; Glass beads; Enzyme immobilization; Non-covalent immobilization; Covalent immobilization; Characterization; PECTIN METHYL ESTERASE; POLYPHENOL OXIDASE; METHYLESTERASE; FRUIT; PECTINMETHYLESTERASE; INACTIVATION; EXTRACTION; SURFACES; Biotechnology & Applied Microbiology; Engineering; Materials Science